Allostrophus cretaceus gen. et sp. nov.: A new polypore fungus beetle (Coleoptera, Tetratomidae) from the Cretaceous Myanmar amber. (December 2018) - Hsiao, Yun; Ślipiński, Adam; Yu, Yali; Deng, Congshuang; Pang, Hong
Abstract: A new species and genus of polypore fungus beetle, Allostrophus cretaceus gen. et sp. nov., is described and illustrated, representing the third documented occurrence of Tetratomidae from Burmese amber (Cenomanian, ca. 99 Ma, Upper Cretaceous). This fossil species can be placed in the extant subfamily Eustrophinae based on the following combination of characters: small-sized, oblong-oval body, narrowed posteriorly; clubbed antennomeres; semicircular pronotum, with two weakly developed subbasal impressions; scutellum without light-colored pubescence and each elytron with traces of eight striae. Morphological characters preserved in the inclusion support the previously proposed high diversity of antennal morphology during the early evolution of eustrophines and suggest the potential fungivory of this extinct species. The new discovery sheds lights on the paleodiversity of mycophagous beetles during the Cretaceous period, strengthening the formerly hypothesized diversification of mushrooms in the late Mesozoic Era.